Modelling the impact of Apivar treatment on a Varroa mite population and the influence of resistance. Issue 2 (20th November 2021) - Almecija, Gabrielle; Poirot, Benjamin; Ventelon, Marie; Suppo, Christelle
Abstract: BACKGROUND: Varroa destructor is a parasite of honeybees. It causes biological damage leading to the colony collapse in the absence of treatment. In recent years, acaricide resistance has emerged in Varroa mites, leading to a decrease in treatment efficacy. We modelled the action of Apivar (amitraz) treatment, using three input parameters: treatment duration, treatment period, and daily mortality due to the treatment. The output parameters were cumulative mite mortality during treatment, the residual number of Varroa mites, and treatment efficacy, expressed as a percentage. RESULTS: The model was validated by monitoring efficacy in the field, in 36 treated hives. According to the model, treatment in the absence of brood is optimal. For a long period without egg laying during the winter, an initial infestation of 100 mites and a start date for treatment of August 7, a minimal treatment efficacy of 98.8% is required for stabilization of the mite population for year to year. More effective treatment is associated with lower cumulative numbers of dead Varroa mites over the entire treatment period. Thus, the total number of dead mites observed during the monitoring of field efficacy provides information about more than just the initial level of colony infestation. The proportion of resistant mites can be modelized by a decrease of daily mortality rate influencing treatment efficacy. Management of the initial Varroa mite infestation of the colony by the beekeeper can compensate for the decrease in treatment efficacy for resistance thresholds of up to 40% of resistant mites. CONCLUSION: Treatment efficacy depends on several parameters, including initial level of infestation, treatment period and the presence of acaricide resistance. Amitraz resistance may lead to treatment failure, even if the beekeeper is able to keep initial infestation rates low. © 2021 Society of Chemical Industry. Abstract : Mathematical modelling: a tool to understand the action of Apivar treatment on the varroa population and to study the influence of different levels of resistance on the treatment efficacy.